2020
DOI: 10.18632/aging.103216
|View full text |Cite
|
Sign up to set email alerts
|

Development of a nomogram that predicts the risk for coronary atherosclerotic heart disease

Abstract: Studies seldom combine biological, behavioral and psychological factors to estimate coronary atherosclerotic heart disease (CHD) risk. Here, we evaluated the associations between these factors and CHD to develop a predictive nomogram to identify those at high risk of CHD. This case-control study included 4392 participants (1578 CHD cases and 2814 controls) in southeast China. Thirty-three biological, behavioral and psychological variables were evaluated. Following multivariate logistic regression analysis, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Moreover, it has been accepted that multiple clinical parameters, such as demographic characteristics, vital signs, laboratory data, and radiological data, are important for the management of patients with CAD, which are usually routinely collected at admission. A previous study indicated that a predictive nomogram based on clinical routine variables is important for early diagnosis and facilitates the development of new prevention and treatment strategies for CAD [ 36 ]. Further, a prospective cohort study has confirmed that incorporating available clinical variables into the existing predictive score is important for prognostic estimation after myocardial infarction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been accepted that multiple clinical parameters, such as demographic characteristics, vital signs, laboratory data, and radiological data, are important for the management of patients with CAD, which are usually routinely collected at admission. A previous study indicated that a predictive nomogram based on clinical routine variables is important for early diagnosis and facilitates the development of new prevention and treatment strategies for CAD [ 36 ]. Further, a prospective cohort study has confirmed that incorporating available clinical variables into the existing predictive score is important for prognostic estimation after myocardial infarction [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some nomogram studies often obscure the classification of patients into normal and abnormal status without focusing on their specific values. For example, some studies simply classified patients into hyperlipidemic and non-hyperlipidemic groups ( 47 ). We used blood lipid, nerve conduction velocity, carotid artery plaque, and other results from medical insurance tests in Chinese patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an evolutionary CAD risk appraisal tool developed from recent information of Chinese population would be better generalized. Some recent studies utilized nomogram to assess CAD risks based on the results of multivariate logistic regression or Cox proportional hazard regression ( 47 50 ). Albeit these studies provided powerful clinical benefits, these models had the inherent drawback that the algorithm is sensitive to multicollinearity and missing values.…”
Section: Discussionmentioning
confidence: 99%